2010
DOI: 10.2146/ajhp090531
|View full text |Cite
|
Sign up to set email alerts
|

Current practices and state regulations regarding telepharmacy in rural hospitals

Abstract: The application of telepharmacy in rural hospitals varies across the United States but is not widespread, and many states have not defined regulations for telepharmacy in hospitals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
55
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 14 publications
5
55
0
Order By: Relevance
“…44 (Currently, telepharmacy is applied to serve remote rural areas, but it may not be limited to rural areas in the future. ), [44][45][46][47][48] • Reconcile medications, 49 • The ASHP Long-Range Vision for the Pharmacy Work Force in Hospitals and Health Systems anticipated that some pharmacy technicians will manage medication supply logistics. 13 While advocating for new models for health-system pharmacy services and for appropriate regulatory provisions, health-system pharmacists should be careful to preserve the freedom to experiment and innovate with respect to the roles of pharmacy technicians.…”
Section: Novel Roles For Pharmacy Techniciansmentioning
confidence: 99%
“…44 (Currently, telepharmacy is applied to serve remote rural areas, but it may not be limited to rural areas in the future. ), [44][45][46][47][48] • Reconcile medications, 49 • The ASHP Long-Range Vision for the Pharmacy Work Force in Hospitals and Health Systems anticipated that some pharmacy technicians will manage medication supply logistics. 13 While advocating for new models for health-system pharmacy services and for appropriate regulatory provisions, health-system pharmacists should be careful to preserve the freedom to experiment and innovate with respect to the roles of pharmacy technicians.…”
Section: Novel Roles For Pharmacy Techniciansmentioning
confidence: 99%
“…Previous studies have focused on describing telepharmacy activities in a small number of hospitals 5,8,[13][14][15][16][17][18][19][20][21] or in a single hospital. 22,23 Studies have reported the impact of telepharmacy by tracking medication error rates, 4 by describing pharmaceutical care activities focused on drug-related problems, 5 by evaluating number of orders reviewed, modified, discontinued, and voided by remote pharmacists, 9 by describing the 24-h pharmacy staffing coverage given, 15 or…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Telepharmacy, which is a subset of telemedicine, may be useful for improving pharmacy service coverage regardless of where the pharmacist is located. [2][3][4] Telepharmacy applies to activities including a combination of electronic data entry, prescription order verification, centralized anticoagulation clinics, online benefit adjudication, medication dispensing, and telehealth consultation with medication use evaluation using computer technology. 1,2 Several rural hospitals in the United States 4 and Australia 5 have implemented telepharmacy services that allow for 24-h pharmacist review of all medication orders.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…12 Although it may be impractical for most rural hospitals to implement many of the costly, labor-intensive processes used at urban hospitals, telemedicine can offer a practical, cost-effective alternative. 5,17,18 …”
Section: Introductionmentioning
confidence: 99%